2014
DOI: 10.1016/j.nuclphysb.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Baryon stability on the Higgs dissolution edge: threshold corrections and suppression of baryon violation in the NMSGUT

Abstract: Superheavy threshold corrections to the matching condition between matter Yukawa couplings of the effective Minimal Supersymmetric Standard Model (MSSM) and the New Minimal Supersymmetric (SO(10)) GUT(NMSGUT) provide a novel and generic mechanism for reducing the long standing and generically problematic operator dimension 5 Baryon decay rates. In suitable regions of the parameter space strong wave function renormalization of the effective MSSM Higgs doublets due to the large number of heavy fields can take th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 103 publications
(171 reference statements)
1
48
0
Order By: Relevance
“…An indication of problems being present already at the matching scale M GUT can be found in the calculation of the threshold corrections [40,41]. The general problem of having large numbers of degrees of freedom (in our case through large representations) and the associated non-perturbativity is a problem, which is far from easy to solve and well beyond the purpose of this paper, although some progress has been made recently [42,43] based on previous works on Seiberg dualities.…”
Section: Jhep05(2015)108mentioning
confidence: 91%
“…An indication of problems being present already at the matching scale M GUT can be found in the calculation of the threshold corrections [40,41]. The general problem of having large numbers of degrees of freedom (in our case through large representations) and the associated non-perturbativity is a problem, which is far from easy to solve and well beyond the purpose of this paper, although some progress has been made recently [42,43] based on previous works on Seiberg dualities.…”
Section: Jhep05(2015)108mentioning
confidence: 91%
“…SO(10) GUTs based on the 210 ⊕ 126 ⊕ 126 Higgs system [2,3] are parameter counting minimal [4]. The version called the new minimal supersymmetric SO(10) grand unified theory (NMSGUT) with the 120-plet fits [5][6][7] all fermion masses and makes distinctive predictions and is thus falsifiable.…”
Section: Introductionmentioning
confidence: 99%
“…It also predicts a normal s-hierarchy, Bino LSP and can yield a light smuon as the next to lightest supersymmetric particle(NLSP), thus promoting a Bino as a good dark matter candidate and making a significant supersymmetric contribution to the muon magnetic moment anomaly. Recently, we showed that careful attention to the quantum communication between the UV completion and its effective theory through the light Higgs portal yields natural and generic suppression of fast proton decay in supersymmetric(SUSY) GUTs [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations